2012
DOI: 10.2337/dc11-1829
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use as a Moderator of Metformin Effect on Risk for Prostate Cancer Among Type 2 Diabetic Patients

Abstract: OBJECTIVEMetformin and statins have shown promise for cancer prevention. This study assessed whether the effect of metformin on prostate cancer (PCa) incidence varied by statin use among type 2 diabetic patients.RESEARCH DESIGN AND METHODSThe study cohort consisted of 5,042 type 2 diabetic male patients seen in the Veteran Administration Health Care System who were without prior cancer and were prescribed with metformin or sulfonylurea as the exclusive hypoglycemic medication between fiscal years 1999 and 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 38 publications
1
46
1
Order By: Relevance
“…[8,9] Furthermore, in the male type 2 diabetic population with a generally high prevalence of dyslipidemia, treatment with both metformin and statin may have a significantly more favorable effect on prostatic cancer incidence than treatment by either medication alone. [10] There was no significant interaction between atorvastatin and metformin. [11] Based on such findings, a fixed-dose combination (FDC) tablet of atorvastatin and metformin sustained-release (SR) was developed for patients with type 2 diabetes with or without dyslipidemia.…”
Section: Introductionmentioning
confidence: 92%
“…[8,9] Furthermore, in the male type 2 diabetic population with a generally high prevalence of dyslipidemia, treatment with both metformin and statin may have a significantly more favorable effect on prostatic cancer incidence than treatment by either medication alone. [10] There was no significant interaction between atorvastatin and metformin. [11] Based on such findings, a fixed-dose combination (FDC) tablet of atorvastatin and metformin sustained-release (SR) was developed for patients with type 2 diabetes with or without dyslipidemia.…”
Section: Introductionmentioning
confidence: 92%
“…[36][37][38][39]. Some studies suggest unexpected variables that might modify the effects of metformin, including pharmacoepidemiologic evidence that exposure to both a statin drug and metformin is necessary for an important antineoplastic effect to be observed ( 40 ) and laboratory evidence that administration of proton pump inhibitors limits cellular uptake of metformin ( 41 ).…”
Section: Pharmacoepidemiology: Hypothesis-generating Cluesmentioning
confidence: 99%
“…10,11) Finally, a recent study suggested statin use moderates the risk of prostate cancer among type II diabetic patients using metformin. 12) Epidemiological studies have shown a reduced risk of advanced prostate cancer with the use of statins. [13][14][15][16] Statin use was also found to be associated with a reduction in the risk of biochemical recurrence in patients with prostate cancer 17) and a decreased risk of cancer mortality.…”
mentioning
confidence: 99%